Approach to the Diagnosis and Management of Common Bleeding Disorders - Rydz, Natalia; James, Paula D. (Seminars in Thrombosis and Hemostasis, 2012)
Mild mucocutaneous bleeding symptoms are common in the general population. Differentiating normal from pathological bleeding complaints begins with a detailed bleeding history that assesses: the pattern (primary versus secondary hemostasis), the severity, and the onset (congenital versus acquired) of bleeding. Bleeding assessment tools have been developed to aid in determining whether bleeding symptoms are outside of the normal range. Although the clinical pattern of bleeding and family history directs laboratory investigations, von Willebrand disease, the most common and best characterized of the primary hemostatic disorders, is often the first diagnosis to be considered. Clinical management focuses on the particular symptoms experienced by the patient. Medical interventions include replacement of the factor that is deficient or defective, or indirect treatments, such as antifibrinolytics (tranexamic acid), desmopression, and hormone-based therapy (e.g., oral contraceptive pill for menorrhagia).
Keywords: mucocutaneous bleeding; bleeding scores; bruising; epistaxis; menorrhagia; von Willebrand disease; hemophilia; platelet function disorder